2005
DOI: 10.2337/diabetes.54.11.3258
|View full text |Cite
|
Sign up to set email alerts
|

Celiac-Superior Mesenteric Ganglionectomy, but Not Vagotomy, Suppresses the Sympathoadrenal Response to Insulin-Induced Hypoglycemia

Abstract: Afferent innervation of the portal vein has been shown to be critical in hypoglycemic detection, but the neural pathway by which these afferents ascend remains unknown. To ascertain the role of vagal afferents versus spinal afferents in hypoglycemic detection, the catecholamine response to hypoglycemia was assessed in male Wistar rats undergoing hepatic vagotomy (HV), total subdiaphragmatic vagotomy (TSV), or celiac-superior mesenteric ganglionectomy (CSMG). After recovering from the surgery, the animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 54 publications
5
66
0
Order By: Relevance
“…[45][46][47] However, more recent data showed that celiac-superior mesenteric ganglionectomy, but not vagotomy, suppressed the response to insulin-induced hypoglycemia, suggesting that the hepatoportal sensor may indeed participate in triggering glucagon secretion. 48,49 In the central nervous system, sites of glucose detection for the control of counter-regulation are present in the hypothalamus and different brainstem nuclei. In the hypothalamus, lesion studies as well as pharmacological and genetic interferences with glucose detection systems have provided evidence for an important role of the VMH in the control of glucagon secretion.…”
Section: Counter-regulationmentioning
confidence: 99%
“…[45][46][47] However, more recent data showed that celiac-superior mesenteric ganglionectomy, but not vagotomy, suppressed the response to insulin-induced hypoglycemia, suggesting that the hepatoportal sensor may indeed participate in triggering glucagon secretion. 48,49 In the central nervous system, sites of glucose detection for the control of counter-regulation are present in the hypothalamus and different brainstem nuclei. In the hypothalamus, lesion studies as well as pharmacological and genetic interferences with glucose detection systems have provided evidence for an important role of the VMH in the control of glucagon secretion.…”
Section: Counter-regulationmentioning
confidence: 99%
“…Hepatoportal glucose sensing ( Figure 2) describes a well-characterized phenomenon by which a glucose gradient established between the portal vein and the hepatic artery is sensed, resulting in increased hepatic glucose uptake, increased peripheral glucose disposal, inhibition of counterregulatory hormone secretion, and inhibition of food intake leading to hypo-glycemia (60,61). The actions of this sensor appear to depend on autonomic afferents to the CNS (62,63). However, the precise cellular composition of this sensor and the mechanism by which it senses and communicates remain uncertain.…”
Section: Molecular and Cellular Glucose Sensingmentioning
confidence: 99%
“…Reportedly, a counterregulatory response to moderate systemic hypoglycemia, i.e. sympathetic efferent activation, is attenuated by clamping the liver at euglycemic levels and is disrupted by interruption of sympathetic (but not vagal) afferents from the hepatic portal circulation [58,59]. Collectively, these observations indicate that the afferent autonomic nervous system, including both vagal and sympathetic nerves, from the hepatoportal structure, plays important roles in conveying information regarding peripheral glucose levels to the brain.…”
Section: B) Signals From the Liver -Liver Functions As An Energy Balamentioning
confidence: 83%